PENGARUH KECERDASAN EMOSIONAL (EMOTIONAL QUOTIENT) DAN LITERASI EKONOMI TERHADAP KESIAPAN MENGAJAR (TEACHING READINESS) - Abdul Rokhim; Albrian Fiky Prakoso (FKIP Unswagati, 2022)
AbstractThis study aims to analyze the effect of emotional intelligence (emotional quotient) and economic literacy on teaching readiness of students of the 2018 and 2019 Economics Education Study Program students, State University of Surabaya. The research data were taken from 86 students who were analyzed using a quantitative approach with structural equation modeling. (SEM) WarpPLS approach. The results showed that emotional intelligence has an influence on economic literacy, the higher the level of emotional intelligence of students, the higher the economic literacy of students. Likewise, emotional intelligence variables affect teaching readiness, so the higher the emotional intelligence of students, the better their teaching readiness. However, the economic literacy variable has no effect on teaching readiness, so students who have high, medium or low levels of economic literacy have no effect on their level of teaching readiness. Thus, the economic literacy variable does not mediate the influence of emotional intelligence on teaching readiness for students of the 2018 and 2019 S1 Economics Education Study Program students, State University of Surabaya.Keywords: Emotional Intelligence, Economic Literacy, Teaching Readiness